Sobre la definición de los dominios transculturales. La antropología del parentesco como teoría sociocultural de la procreación - Aurora González Echevarría (Alteridades, 2010)
Since the sixties the classic anthropology of kinship was severely criticized because the polisemic charac-terization of its contents and the uncritical repetition of XIXth century theoretical models. Although some of them are based on unsound science theories, we sus-tain in this article that based on the radical criticisms of needham and schneider, the anthropology of kinship in particular and anthropology in general, have to choose between carefuly defining their analytical concepts and boundaries or dropping transcultural theory altogether. A comparative study of kinship should begin with an analytical and transcultural definition of its domain that is not only relevant but also fruitful and able to provide a comprehensive theoretical explanation of the differences and similarities of kinship patterns.